A new luminescent Cd(ii)-MOF as a highly selective chemical probe for Fe3+ in aqueous solution with mixed metal ions. Issue 110 (23rd October 2015) - Wu, Yunlong; Yang, Guo-Ping; Zhang, Yingdi; Shi, Nannan; Han, Jun; Wang, Yao-Yu
Abstract : A new luminescent Cd(ii )-MOF has been prepared by solvothermal reaction. The luminescent properties were investigated in detail, showing a highly selective sensitivity for sensing Fe 3+ in aqueous solution with mixed metal ions. Abstract : A new metal–organic framework (MOF) with the formula [Cd(H2 La )0.5 (H2 Lb )0.5 (H2 O)] (1 ), where H2 La 2− and H2 Lb 2− represent two different coordination modes of H2 L 2− ligands (H4 L = [1, 1′:4′, 1′′-terphenyl]-2′, 4, 4′′, 5′-tetracarboxylic acid), has been synthesized successfully by solvothermal reaction, and characterized by elemental analysis, FT-IR spectroscopy, powder X-ray diffraction (PXRD), and thermogravimetric analysis (TGA). Interestingly, H2 L 2− adopted two coordination fashions during the self-assembly process of1 because of the effect of partially deprotonated H4 L ligands, which resulted in the 3D framework of1 showing a trinodal (4, 4, 4)-connectedPtS topology with a point symbol of (4 2 ·8 4 ). More importantly, the product of1 displays greatly intense luminescence in the solid state and high sensitivity and selectivity for Fe 3+ ions in aqueous solution with mixed ions, making it a new potential probe for detecting Fe 3+ . The quenching mechanisms are also further discussed in detail.